Existence and Comparative Statics in Heterogeneous Cournot Oligopolies - Hoernig, Steffen (2019)
We prove the existence of symmetric pure Cournot equilibria with heterogeneous goods under the following condition: Each firm reacts to a rise in competitors' output in such a way that its market price does not rise. This condition is not related to whether goods are strateigc substitutes or complements. we establish that maximum and minimum equilibrium prices are decreasing as more firms enter if competitors' outputs enter inverse demand aggregated; for non-aggregative demand prices may increase. Total quantity increases only if each firm's market price is more affected by its own output than competitors' outputs.